(untitled) (Canadian Eye Care Today, 2023)
Inherited retinal degenerations (IRDs) are of great interest with the development of novel therapies, thereby allowing this group of conditions to be “actionable” for the first time. A molecular diagnosis can be obtained in nearly 70% of cases of IRD, with over 300 IRD-linked genes having been identified to date. Numerous animal models of different genetic subtypes of IRDs replicated the human phenotypes enough to develop and test novel therapies to improve outcomes for IRD patients. The first gene replacement therapy indicated for IRD, Luxturna (voretigene neparvovec-rzyl), was approved by Health Canada in October 2020 and is now available to patients with vision loss due to inherited retinal dystrophy caused by confirmed biallelic RPE65 mutations. Clinicians from Ontario, Quebec and Alberta can now access this treatment through their province’s public health plan. This article aims to review some basic information and present new knowledge about IRDs to allow clinicians to better understand diagnosis and disease management.